Development of the photo-diode subsystem for the HERD calorimeter double-readout. (1st September 2022) - Adriani, O.; Antonelli, M.; Basti, A.; Berti, E.; Betti, P.; Bigongiari, G.; Bonechi, L.; Bongi, M.; Bonvicini, V.; Bottai, S.; Brogi, P.; Castellini, G.; et al.
Abstract: The measurement of cosmic-ray individual spectra provides unique information regarding the origin and propagation of astro-particles. Due to the limited acceptance of current space experiments, protons and nuclei around the "knee" region (∼ 1 PeV) can only be observed by ground based experiments. Thanks to an innovative design, the High Energy cosmic-Radiation Detection (HERD) facility will allow direct observation up to this energy region: the instrument is mainly based on a 3D segmented, isotropic and homogeneous calorimeter which properly measures the energy of particles coming from each direction and it will be made of about 7500 LYSO cubic crystals. The read-out of the scintillation light is done with two independent systems: the first one based on wave-length shifting fibers coupled to Intensified scientific CMOS cameras, the second one is made of two photo-diodes with different active areas connected to a custom front-end electronics. This photo-diode system is designed to achieve a huge dynamic range, larger than 10 7, while having a small power consumption, few mW per channel. Thanks to a good signal-to-noise ratio, the capability of a proper calibration, by using signals of both non-interacting and showering particles, is also guaranteed. In this paper, the current design and the performance obtained by several tests of the photo-diode read-out system are discussed.